Improvement Design for The Effectiveness of Tracer Studies Process in Bandung’s Private University - Mochamad Fabian Redhatama; Wiyono Sutari; Heriyono Lalu (Institut Teknologi Sepuluh Nopember, 2020)
A concrete step to obtain information is to have a good management information system. For universities, one of the most important information is about alumni or graduate’s feedback. However, the actual management information system in several Bandung’s private university cannot provide the information desired by the department and the tracer studies response rate is far from good. Which means the tracer study process needs to be re-engineered. Thus, this research aims to redesign the business processes by analyzing the “As-Is”. This research found that a good tracer study system needs to build a good relationship with the alumni. So that, this research proposes the key success factor for the effectiveness of tracer studies in Bandung’s private universities. Since the response rate is one of the key indicators of tracer studies, supposed that in order to increasing the response rate. The universities should create good relationships with the alumni since they were in sophomore year with their guardian lecturer and thesis’ promotor. Thus, this reengineered process should be useful in order to increase the tracer studies process productivity that measured by response rate to supports national data collection and comparisons for better education curriculum evaluations.